Cognitive Changes In Stroke Patients Following Robotic Rehabilitation - Razak, Wan Adibah Nadiah Abd (2022)
Stroke continues to be a serious healthcare issue that has significant impact on the cognition. Different interventions are available for post-stroke patients to bounce back healthy again after obtaining a number of difficulties due to the stroke. Thus, the objective of this study is to investigate the effect of robotic rehabilitation and conventional rehabilitation on the cognition; specifically through the domains of general cognition, memory, and attention. A randomized trial design was used on a sample of post-stroke patients undergoing rehabilitation at Hospital Universiti Sains Malaysia and the participants were recruited through convenient sampling. The total number of participants that were obtained are ten, six from the robotic group and four from the conventional group. The participants were assessed twice using Wechsler Abbreviated Scale of Intelligence – 2nd Edition (WASI-II), Wechsler Memory Scale – 3rd Edition (WMS-III), and Comprehensive Trail Making Test (CTMT). The first assessment was done at the initial stage of the intervention and another assessment was done after a one month duration. The outcome of this study found that robotic rehabilitation has a higher improvement in terms of the cognitive domains of memory and attention, as opposed to conventional rehabilitation. The limitations of this study includes the sample size, accessibility of participants and time limitation. Despite the limitations found throughout the study, the findings have contributed to the understanding of the efficacy of robotic rehabilitation in the aspect of cognition because robotic rehabilitation is fairly new to Malaysia and the contributions of this findings act as a literary contribution to the field of rehabilitation medicine.